2020
DOI: 10.1186/s43093-020-00029-6
|View full text |Cite
|
Sign up to set email alerts
|

A cause and effect relationship between FIIs, DIIs and stock market returns in India: pre- and post-demonetization analysis

Abstract: In one of the most historic decisions in the Indian economy, the Government of India demonetized its two highest currency notes (Rs. 500 and Rs. 1000) on November 8, 2016. The Indian stock market does not only consist of domestic investors; however, it does attract a large pool of foreign investors. The present study, considering the significance of demonetization in Indian economy, attempted to examine the association between foreign institutional investment (FII), domestic institutional investment (DII) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A similar study by Alam (2020) examining select South Asian economies found that inflation rates and GDP had a significant impact on stock returns. However, Nurasyikin et al (2017) found no link between money supply changes and stock index returns across three ASEAN countries. Chandrashekar (2018) compared the response of Brazil's and India's stock prices to a host of macroeconomic variables including inflation and interest rates, and found that there was a significant and positive relationship between stock prices and macroeconomic variables for each of the countries.…”
Section: Demonetisationmentioning
confidence: 70%
“…A similar study by Alam (2020) examining select South Asian economies found that inflation rates and GDP had a significant impact on stock returns. However, Nurasyikin et al (2017) found no link between money supply changes and stock index returns across three ASEAN countries. Chandrashekar (2018) compared the response of Brazil's and India's stock prices to a host of macroeconomic variables including inflation and interest rates, and found that there was a significant and positive relationship between stock prices and macroeconomic variables for each of the countries.…”
Section: Demonetisationmentioning
confidence: 70%
“…Regression analysis is a very old technique researchers and statisticians use to diagnose a cause-and-effect relationship between two or more variables [118]. The measures used for the statistically significant relationship based on regression are t and p values.…”
Section: Hypothesis Testing (Direct Relationships)mentioning
confidence: 99%
“…The constant interdependence among the financial markets like equity, bond, commodity, stock, etc. propagate intensification of the financialization and enhanced price volatility (Parab & Reddy, 2020). Multiple alternatives are available for the investors to diversify their investment portfolios because of financialization of securities (Domanski & Heath, 2007;Dwyer, Gardner & Williams, 2011;Vivian & Wohar, 2012;Silvennoinen & Thorp, 2013).…”
Section: Introductionmentioning
confidence: 99%